2004
DOI: 10.1212/01.wnl.0000144339.34733.e9
|View full text |Cite
|
Sign up to set email alerts
|

Early epidural blood patch in spontaneous intracranial hypotension

Abstract: Thirty patients with a typical orthostatic headache were treated by early lumbar epidural blood patch (EBP) without previously performing lumbar puncture or identifying a CSF leak and with or without typical MRI changes. A complete cure was obtained in 77% of patients after one (57%) or two (20%) EBPs. Spontaneous intracranial hypotension with typical orthostatic headache can be diagnosed without lumbar puncture and can be cured by early EBP in a majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
163
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(168 citation statements)
references
References 10 publications
1
163
1
3
Order By: Relevance
“…The placement of an epidural blood patch is the most commonly used initial treatment technique for spontaneous intracranial hypotension, and most patients react favorably to an epidural blood patch, even if only temporarily. 1,17,18 The improvement in symptoms after an epidural blood patch is not limited to positional headaches but also includes other types of headache, as well as the associated symptoms, including coma. [6][7][8][9][10][11][12][13][14] However, most patients require 2 or more epidural blood patches, and improvement may be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The placement of an epidural blood patch is the most commonly used initial treatment technique for spontaneous intracranial hypotension, and most patients react favorably to an epidural blood patch, even if only temporarily. 1,17,18 The improvement in symptoms after an epidural blood patch is not limited to positional headaches but also includes other types of headache, as well as the associated symptoms, including coma. [6][7][8][9][10][11][12][13][14] However, most patients require 2 or more epidural blood patches, and improvement may be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal MR imaging results, particularly the enhancement of the pachymeninges, have been considered to be the sine qua non of spontaneous intracranial hypotension, 22 but it has become well established that a sizeable minority of patients (28% in our study) have normal results on brain MR imaging. 1,18 If a patient suspected of spontaneous intracranial hypotension has a normal brain MR imaging result and no CSF leak on spinal imaging, a confirmatory diagnosis can still be made with the diagnostic criteria on the basis of a low opening pressure, the presence of spinal meningeal diverticula, and resolution of symptoms after an epidural blood patch. Although this diagnostic category may seem to be less robust, surgical exploration of the spinal meningeal diverticula confirmed the presence of a CSF leak in all 3 such treated patients in this category.…”
Section: Discussionmentioning
confidence: 99%
“…5 Large-volume lumbar epidural blood patches, an approach adapted from the treatment of post-lumbar puncture headache, are often used for treatment of spontaneous intracranial hypotension and can be effective immediately. 6 However, it remains unclear how such therapy might actually address the underlying problem of spontaneous CSF leaks, given that when visualized, these leaks are most commonly observed in the thoracic region, not the lumbar region. 7 One possibility is that these nondirected "patches" increase CSF pressure by displacement of volume in the spinal canal, thereby alleviating symptoms until spontaneous closure of leaks can occur.…”
Section: Discussionmentioning
confidence: 99%
“…9 Prior authors have reported symptomatic improvement rates ranging from 50% to 100% with site-directed epidural blood/fibrin patch procedures by using CT or fluoroscopic guidance. [10][11][12][13][14][15] These treatment options, however, often require epidural punctures in the upper thoracic and cervical spine. Epidural puncture in these regions is technically more challenging due the anatomy and the epidural space becoming smaller as you ascend from the lumbar to the cervical region.…”
Section: Discussionmentioning
confidence: 99%